Three simple and cost-effective assays for AAC(6′)-Ib-cr enzyme activity - Liang, Shizhou; Cai, Wenpin; Mao, Ruiben; Chen, Mengquan; Dai, Xianning; Jin, Xiaoli; Kong, Wanzhong (Frontiers in Microbiology, 2025)
The enzyme AAC(6′)-Ib-cr belongs to plasmid-mediated quinolone resistance (PMQR), first reported in 2006 and now widely disseminating. Here, we developed three phenotypic methods to detect AAC(6′)-Ib-cr enzyme-producing Enterobacteriaceae (APE), two of which are proposed innovatively in this research. These tests are based on the following principles: (i) Matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF MS) can measure the mass shift of 42 Da resulting from ciprofloxacin acetylation by the AAC(6′)-Ib-cr enzyme. (ii) Co-incubation of ciprofloxacin disks with APE results in inactivation of the drug activity, making it unable to inhibit the growth of the indicator organism. We named this test the quinolone inactivation method (QIM). (iii) Based on the principles of the modified Hodge test, we designed the quinolone Hodge test (QHT). Through exploration of optimal conditions for three methods, we found that MALDI-TOF MS provides the most intuitive results after 1 h of incubation. The interpretability of the QIM and QHT results was significantly improved when the indicator organism E. coli ATCC25922 was replaced with a quinolone-slightly-resistant isolate. However, Proteus mirabilis was excluded from both QIM and QHT due to its swarming motility. Next, a validation study was conducted using a prospectively collected set of 187 clinical strains, demonstrating 100% specificity (MSM: 141/141; QIM, QHT: 135/135) and 100% sensitivity (MSM: 46/46; QIM, QHT: 33/33) compared to the genotype. In a word, this study presented three simple, efficient, and cost-effective methods for detecting APE, suitable for clinical microbiology laboratories under various conditions for the prevention and control of hospital infections.